Pengaruh Independensi, Pengetahuan Keuangan, dan Gender Komite Audit Terhadap Ketidakpatuhan Pengungkapan Keuangan (Studi Kasus Pada Perusahaan Publik yang Mendapat Teguran Publik Oleh Bursa Malaysia Tahun 2014-2020) - Nurliani, Dinda; Icih, Icih (Jurnal Akuntansi dan Keuangan, 2022)
This research aims to determine the influence of independence, financial knowledge, and gender audit committees on non-compliance with financial disclosure. The independent variables in the study were the independence, financial knowledge, and gender of the audit committee. The study sample represents 19 companies that were publicly reprimanded by Bursa Malaysia in the period 2014-2020. Sampling method using purposive sampling method. Data analysis methods use logistic regression methods. The results of this study showed that the independence, financial knowledge, and gender of the audit committee had no effect on the non-compliance of financial disclosures. However, if assessed simultaneously the variables of independence, financial knowledge, and gender of the audit committee affect the non-compliance of financial disclosure.